A STUDY OF THE IMPACT OF MODERN TECHNOLOGY ON THE WORK AND WORKING CONDITIONS OF AGRICULTURAL LABORERS - Pratibha Sinha (International Journal of Multidisciplinary Research and Studies, 2021)
Over the course of the last half-century, advancements have been made in the field of sustainability. For example, the best management practises agricultural sector and policies that have been updated for the benefit of agriculture are extensively adopted and have been effective at highlighting the need of external inputs to rise in today's society. Reduced susceptibility to illness thanks to newly developed hybrids. the manufacture of food This has resulted in an increase in the use of pesticides, biological methods of pest management, cultural practises, inorganic fertiliser, and animal intake of pesticides, all of which have the potential to lower the occurrence of illnesses and pests. products for animal feed as well as tractors and other types of machinery. These insect-specific chemicals and biological insect controls are now being used instead of broad-spectrum treatments and procedures because they are foreign inputs that have replaced for natural resources. As a result, the effectiveness of these treatments has been reduced. Insecticides pesticides, which actually cut down on the amount of sprays needed, have largely replaced the biological, cultural, and mechanical approaches that were formerly utilised, and consequently their capitals. GIS, Crop models as well as methods for preventing and treating diseases, weeds, and insects.